Religion, human rights and constitutional contract politics in Malaysia - Mohamad, Marzuki (IIUM Press, International Islamic University Malaysia, 2008)
The debate about human rights in Malaysia took a new turn in the early twenty-first century when it started to focus on the issue of religious freedom. The proponents of secular-liberal notion of religious freedom argued that religious and racial harmony would be better achieved if Malaysians of all races and religions enjoy absolute religious freedom, which includes the right to renounce Islam. However, the secular-liberal approach to religious freedom, contrary to the expectation of its proponents, accentuates religious and racial division in Muslim-majority Malaysia.